Predictors of health-related quality of life among Hispanic and non-Hispanic White breast cancer survivors in New Jersey. Issue 5 (3rd September 2021) - Almatkyzy, Gulaiim; Mojica, Cynthia M.; Stroup, Antoinette M.; Llanos, Adana A.M.; O'Malley, Denalee; Xu, Baichen; Tsui, Jennifer
Abstract: Purpose: To examine predictors of health-related quality of life (HRQoL) in Hispanic and non-Hispanic White (NHW) breast cancer (BC) survivors. Design: Cross-sectional study using survey data. Participants: Women diagnosed with BC at ages 21-79 years, between 2012-2014, recruited from the New Jersey State Cancer Registry. Methods: HRQoL was assessed using the Functional Assessment Cancer Therapy (FACT-G) instrument. Descriptive statistics compared Hispanics and NHWs, and multivariate regression analyses identified predictors of HRQoL. Results: HRQoL was significantly higher scores among NHW (85.7 ± 18.5) than Hispanics (79.4 ± 20.1) (p < 0.05). In multivariate analyses, comorbidities (β: −13.3, 95%CI: −20.6, −5.92), late-stage diagnosis (β: −5.67, 95%CI: −10.7, −0.62), lower income (β: −13.9, 95%CI: −19.8, −7.97) and younger age at diagnosis were associated with lower HRQoL. Conclusion: Socio-demographic and clinic characteristics were significant predictors of HRQoL among diverse BC survivors. Implications for Psychosocial Oncology: Supportive psychosocial care interventions tailored to the needs of young, low-income BC survivors with comorbidities are needed.